PENYULUHAN DAN PELATIHAN BUDIDAYA IKAN TAWAR SISTEM AIR DERAS BAGI WARGA DESA PANCASAN, AJIBARANG, KABUPATEN BANYUMAS - Sri Lestari; Nuning Vita Hidayati; Refius Pradipta Setyanto; Weni Novandari; Etin Pujihastuti; Lasmedi Afuan (Jurnal Abdi Insani, 2023)
The aquaculture industry within the fisheries sector is experiencing ongoing expansion, driven by advancements in technology and a rising demand in the market. One emerging method in the cultivation of freshwater fish involves the utilization of a running water system. This technique is being developed due to its advantageous characteristics, such as its ability to effectively manage water quality and its potential for achieving high levels of productivity. The implementation of this approach has commenced by the Mina Sehat and Mina Depok Fish Cultivator Groups (Pokdakan) in Pancasan Village, Ajibarang, Banyumas. The purpose of this program was to offer instruction and enhance the knowledge of the Pokdakan and Pancasan Village community in rapid water system fish cultivation techniques. In addition to this, a feasibility study was conducted to assess the viability of aquaculture practices. The process of this activity involves several key elements, namely planning, counseling, surveying cultivation demonstration plot locations, and evaluation. Training is facilitated by the utilization of presentations and feasibility assessments, with active engagement from the community in various endeavors. The preparation for the activities involved the development of an activity plan, followed by coordination with the Maritime and Fisheries Training and Extension Center (Puslatluh KP), the Head of Pancasan Village, BUMDES Berkah Banyu Makmur, and Pokdakan Mina Sehat and Mina Depok. During the preliminary phase, Jenderal Soedirman University (UNSOED) and Puslatluh KP have offered technical assistance and outreach programs to fish farmer groups, aiming to equip them with the necessary knowledge and abilities in fish cultivation utilizing the fast water system. The subsequent phase entails conducting a site survey and feasibility assessment of the cultivation site. According to the findings of the study, the current cultivation location satisfies the prerequisites for the efficient growing of fast water fish. However, it is necessary to make certain adjustments to the design and construction of the pond in order to optimize its functionality. The implementation of the proposed agricultural system is expected to yield increased fish output in Pokdakan and the Pancasan Village community, hence enhancing their overall wellbeing.